Possibilities and normative bases for involving students and young people in scientific research activities in our republic (Eurasian Journal of Research, Development and Innovation, 2025)
In our republic, large-scale measures are being implemented to improve the scientific potential of pedagogical teams by reforming the education system, raising the training of scientific personnel to the level of modern requirements, and attracting creativelyminded, talented young people to scientific research activities. The government of Uzbekistan considers education to be a priority area for all stages of reforms. The main link in education is science and its continuous development. Therefore, the main component of the national personnel training model is: science - training highly qualified specialists and their users, developing advanced pedagogical and information technologies.